ISSUES OF IMPROVING TAX ADMINISTRATION REGARDING PERSONAL INCOME TAX CALCULATION IN UZBEKISTAN - Yadgarov Sherzod Kholmurotovich (Web of Journals Publishing, 2024)
The article highlights, based on a study of the best practices of foreign countries in improving tax systems, it is necessary to develop a scientific proposal and practical recommendations on ways to improve this tax, taking into account the requirements of the present time.
Keywords: individuals, income tax on individuals, state budget, income.